2008
DOI: 10.1371/journal.ppat.1000082
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Host Barriers Restrict Poliovirus Trafficking in Mice

Abstract: RNA viruses such as poliovirus have high mutation rates, and a diverse viral population is likely required for full virulence. We previously identified limitations on poliovirus spread after peripheral injection of mice expressing the human poliovirus receptor (PVR), and we hypothesized that the host interferon response may contribute to the viral bottlenecks. Here, we examined poliovirus population bottlenecks in PVR mice and in PVR mice that lack the interferon α/β receptor (PVR-IFNAR−/−), an important compo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
163
1
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 107 publications
(176 citation statements)
references
References 49 publications
(86 reference statements)
11
163
1
1
Order By: Relevance
“…Studies of poliovirus infection in mouse models indicate that multiple factors influence infection by the enteral route, including PVR expression, innate immunity, mucosal integrity, and interactions with intestinal flora (40,48,49). A major difference between the mouse models of poliovirus and CVB3 infection is that, unlike poliovirus, CVB3 has a natural receptor in mice, murine CAR; once CVB3 enters the bloodstream, infection can spread readily in the absence of any transgenic receptor.…”
Section: Discussionmentioning
confidence: 99%
“…Studies of poliovirus infection in mouse models indicate that multiple factors influence infection by the enteral route, including PVR expression, innate immunity, mucosal integrity, and interactions with intestinal flora (40,48,49). A major difference between the mouse models of poliovirus and CVB3 infection is that, unlike poliovirus, CVB3 has a natural receptor in mice, murine CAR; once CVB3 enters the bloodstream, infection can spread readily in the absence of any transgenic receptor.…”
Section: Discussionmentioning
confidence: 99%
“…Studies of the retrograde transneuronal transmission of poliovirus identified a bottleneck during axonal transport (3,26). Kuss et al marked poliovirus genomes with nucleic acid "bar codes" to follow spread of infection of virus populations into the PNS and CNS (27). In these studies, population diversity diminished as the length of axon increased.…”
Section: Discussionmentioning
confidence: 99%
“…In some cases, this expansion eventually becomes irremediable on a small spatiotemporal scale; local host defenses are no longer able to contain infection, and the virus is established at the main sites of replication, a state that is generally referred to as systemic infection. In many viral pathosystems, the transition from primary infection to systemic infection is labyrinthine: the host immune system effectuates different defensive mechanisms, and on the other hand, different infection pathways are accessible to the virus (10,23). This great complexity has made it difficult to study interactions within the virus population during the establishment of systemic infection.…”
mentioning
confidence: 99%